EFFECTIVENESS OF LEAF EXTRACT REDUCE INFLAMMATION REACTION IN HYPERCHOLESTEROLEMIA RATS - Puguh Santoso; Ni Nyoman Wahyu Udayani; I Nyoman Gede Tri Sutrisna; Ketut Agus Adrianta (Institute for Research and Community Services Udayana University, 2017)
Abstract High blood cholesterol is often called hypercholesterolemia is a risk factor for the emergence of pathological conditions such as heart and blood vessel disease. Hypercholesterolemia has an important role in the occurrence of damage to the endothelial cells is mainly caused by oxidized LDL. Oxidation of LDL triggers the formation of TNF - ?. Leaves messengers that allegedly contains flavonoids can improve the situation of hypercholesterolemia through the barriers specifically the expression of TNF - ? increased due to hypercholesterolemia. Plants messengers known to contain alkaloids, flavonoids, tannins, saponins, polyphenols, calcium oxalate, fats, and essential oil. Flavonoids which has the ability to bind the atom to form free radicals not to excess free radicals, thereby inhibiting the oxidative modification of LDL become ox-LDL so it will not be formed atherosclerosis. This study uses the Randomize pattern Pre and Post Test Control Group Design, using white rats (Rattusnovergicus) with Wistar strain aged 3-4 months, weighing 175-200 grams. Divided into four groups: Group I as a control with placebo, Group II treatment using extracts of ethanol leaves a messenger at a concentration of 10%, Group III treatments using extracts of ethanol leaves a messenger at a concentration of 20%, Group IV is to use the extract ethanol leaves errand at a concentration of 30%. It can be concluded at 4 dose group 30% messengers leaf extract significantly different, p <0.05, so it can be said that the provision of effective messengers extract at a dose of 30%.